2018
DOI: 10.1111/jnu.12442
|View full text |Cite
|
Sign up to set email alerts
|

Migrants’ Healthcare Experience: A Meta‐Ethnography Review of the Literature

Abstract: Purpose Worldwide, more than 214 million people have left their country of origin. This unprecedented mass migration impacts health care in host countries. This article explores and synthesizes literature on the healthcare experiences of migrants. Design A meta‐ethnography study of qualitative studies was conducted. Methods Eight databases (Medline, the Cumulative Index to Nursing and Allied Health Literature [CINAHL], PsycINFO, Embase, Web of Science, Migration Observatory, National Health Service Scotland Kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 27 publications
1
36
0
Order By: Relevance
“…The migrant population is diverse and each person has individual health needs (Luiking et al, 2018). Indeed, the most recent project conducted by our research group, a meta ethnography study (Luiking et al, 2018) showed that a multitude of factors influence the HCSB decision-making process.…”
Section: Healthcare-seeking Behaviour: Influencing Factorsmentioning
confidence: 98%
See 3 more Smart Citations
“…The migrant population is diverse and each person has individual health needs (Luiking et al, 2018). Indeed, the most recent project conducted by our research group, a meta ethnography study (Luiking et al, 2018) showed that a multitude of factors influence the HCSB decision-making process.…”
Section: Healthcare-seeking Behaviour: Influencing Factorsmentioning
confidence: 98%
“…Indeed, the most recent project conducted by our research group, a meta ethnography study (Luiking et al, 2018) showed that a multitude of factors influence the HCSB decision-making process. Migrants seek care according to their needs and legal status and they often consult trusted individuals within their own community about how to address a health problem before seeking formal help (Luiking et al, 2018). Further considerations are time and financial resources (Herdman et al, 2016;Lattof, 2018).…”
Section: Healthcare-seeking Behaviour: Influencing Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Asylum seekers are in a vulnerable situation due to unpleasant experiences and exposures in their home countries and during migration. 4 , 5 Previous research 35 , 7 , 8 reports that the health examination can be a burden for them due to poor communication and information, cultural barriers and misunderstandings, unmet needs and expectations, feelings of ambiguity, mistrust and insecurity and the experience of being more an object than a unique individual. Asylum seekers also reported that their psychological and emotional needs and problems are overlooked during the health examination, 6 , 9 even though these are known to be significant health problems for asylum seekers.…”
Section: Introductionmentioning
confidence: 99%